Building Health System Resilience in Africa During the COVID-19 Pandemic - Aanuoluwapo Adeyimika Afolabi; Olayinka Stephen Ilesanmi (University of New South Wales, 2022)
Many essential health services have been paused because of the COVID-19 pandemic. To ensure that adequate health delivery is not impeded during the COVID-19 pandemic, this study aimed to describe the strategies for building health system resilience in Africa during the COVID-19 pandemic. The integration of COVID-19 care into routine healthcare delivery across African countries should be prioritized. Investment in human and material resources for the health sector should be prioritized by policymakers. Adequate community engagement should be prioritized across all communities in Africa. Investment in leadership development training across all health sectors would promote initiative-driven decision making and promote infection control practices in health facilities.